IFITM3, FURIN, ACE1, and TNF-α Genetic Association With COVID-19 Outcomes: Systematic Review and Meta-Analysis - de Araújo, João Locke Ferreira; Menezes, Diego; Aguiar, Renato Santana de; Souza, Renan Pedra de (Frontiers in Genetics, 2022)
Human polymorphisms may contribute to SARS-CoV-2 infection susceptibility and Covid-19 outcomes (asymptomatic presentation, severe Covid-19, death). We aimed to evaluate the association of IFITM3, FURIN, ACE1 and TNF-α genetic variants with both phenotypes using meta-analysis. The bibliographic search was conducted on the PubMed and Scielo databases covering reports published until February 8th, 2022. Two independent researchers examined study quality using the Q-Genie tool. Using the Mantel-Haenszel weighted means method, odds ratios were combined under both fixed- and random-effect models. Twenty-seven studies were included in the systematic review (five with IFITM3, two with Furin, three with TNF-α and 17 with ACE1) and 22 in the meta-analysis (IFITM3 n=3, TNF-α and ACE1 n=16). Meta-analysis indicated no association of (1) ACE1 rs4646994 and susceptibility; (2) ACE1 rs4646994 and asymptomatic Covid-19; (3) IFITM3 rs12252 and ICU hospitalization; (4) TNF-α rs1800629 and death. On the other hand, significant results were found for ACE1 rs4646994 association with Covid-19 severity (11 studies, 692 severe cases, 1433 non-severe controls). The ACE1 rs4646994 deletion allele showed increased odds for severe manifestation (OR: 1.45; 95%CI: 1.26 – 1.66). The homozygous deletion was a risk factor (OR: 1.49, 95% CI: 1.22 - 1.83), while homozygous insertion presented a protective effect (OR: 0.57, 95% CI: 0.45 – 0.74). Further reports are needed to verify this effect on populations with different ethnic backgrounds